Versatility in Mandibular Reconstruction after Ablative Tumor Surgery, Single Center Experience - Mohamed Tarek Hafez; Khaled Abdel Wahab; Sameh Roshdy; Fayez Shahatto; Waleed el Nahas; Mohamed El Metwally; Fathy Denewer; Omar Farouk; Adel Denewer (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2016)
Mandibular reconstruction using vascularized osteocutaneous flaps is necessary to improve functional outcomes, such as jaw movement and mastication, and aesthetics after the wide resection of the mandible [1]. Bone grafts had been widely used for reconstruction, with the advent of microsurg ry, such as rib [2], metatarsal [3], radial [4], scapular [5], iliac [6], and fibular [7,8]. Using the fibula for re on truction of mandibular defects  through microvascular technique was first described by Hidalgo in 1989 [9]. This microvascular flap depends on peroneal artery and the  accompanying veins. This flap is characterized by rich vascularity  with a long and wide pedicle as the vascular nourishment to this bone comes through both segmental and intraosseous ways, so, it can withstand multiple osteotomies without fear from any ischemic complications [10]. This makes reconstruction of large defects after radical tumor resection more easy.